الاستكشافات الجغرافية واثرها على افريقيا واوروبا - Al-Kufi, ا.م. محمد عبد الحميد جاسم; Kadhim, م. رشا فاضل (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
The geographical explorations of the continent of Africa gained special importance because of its important role in the incursion to reach the road to India, which was the desired goal for the countries of Europe to achieve the colonial purpose. A number of objective factors that prompted us to choose the topic have contributed, including that it is a topic that academic studies did not address in the research, in addition to its importance in shedding light on the impact of geographical explorations on various aspects of the African and European reality, which made me address its study in an introduction, five points and a conclusion. The first point dealt with: (the delay in discovering Africa and its causes), while the second point dealt with: (the factors that led to geographical explorations), and the third point included: (the stages of the discovery of Africa), as well as its role in the succession of journeys until reaching the road to India, and the fourth point was discussed: (the most important countries that led the exploration movements), and the most prominent reasons for their precedence or delay in reaching the coasts of Africa, and the fifth point included: (the results of the geographical exploration movement) and the exploitation by European countries of the regions of Africa in various fields to achieve the colonial goal. The conclusion came to clarify the most important findings of the research, and it was relied on a group of books, foremost of which stands in the book of Shawqi Al-Jamal, Abdullah Abdul-Raziq Ibrahim: (The Modern and Contemporary History of Africa), which is an important source in covering the topic, in addition to providing the research with valuable information. Existing in letters and theses, the most prominent of which was the doctor's thesis by researcher Hussein Jabbar Shukr: (Political developments in the Congo), the importance of helping the researcher obtain information.